Study of the electrical properties of radiation hard devices based on III-V materials - Hasbullah, Nurul Fadzlin; Alam, A. H. M. Zahirul ([s.n], 2012)
In this fast developing era of technological advancement, semiconductor devices hold vital key due to its vast usefulness in every integrated circuit. Most electronic devices nowadays are fabricated using semiconductor materials. GaAs is preferred over silicon to produce devices due to it being more resistant to defects due to radiation. However, literature has proven that defects due to radiation are dependent on the type of radiation and material of the device. Exposure to neutrons can produce measurable changes in the electrical properties and degradations of various semiconductors such as displacement damage effects and indirect ionization. This research studies the effects of neutron radiation by analyzing its current-voltage (I-V) characteristics and comparing it to the commercial silicon or GaAs diodes. The results of neutron radiation using the pneumatic transfer system show leakage current increment in all diodes after bombardment. The increase in leakage current is interpreted as being due to an increase of generation-recombination traps created in the band gap after radiation which indicates device degradation. However the GaAs infrared emitting diode showed a higher leakage current increment compared to the silicon switching diodes. This may be due to gold doping in silicon which may reduce the effects of neutron irradiation by restricting the formation of other energy levels in the bandgap (McPherson et al. 1997).